MicroRNA-27a Promotes Oxidative-Induced RPE Cell Death through Targeting FOXO1. (1st November 2021) - Ren, Chengda; Hu, Weinan; Wei, Qingquan; Cai, Wenting; Jin, Huizi; Yu, Donghui; Liu, Chang; Shen, Tianyi; Zhu, Meijiang; Liang, Xiuwei; Yu, Jing
Abstract : Age-related macular degeneration (AMD) is a multifactor disease, which is primarily characterized by retinal pigment epithelium (RPE) cell loss. Since the retina is the most metabolically active tissue, RPE cells are exposed to consistent oxidative environment. So, oxidation-induced RPE cell death has long been considered a contributor to the onset of AMD. Here, we applied a retinal degeneration (RD) rat model induced by blue light-emitting diode (LED) and a cell model constructed by H2 O2 stimulus to mimic the prooxidant environment of the retina. We detected that the expression of miR-27a was upregulated and the expression of FOXO1 was downregulated in both models. So, we furtherly investigated the role of miR-27a-FOXO1 axis in RPE in protesting against oxidants. Lentivirus-mediated RNA was injected intravitreally into rats to modulate the miR-27a-FOXO1 axis. Retinal function and histopathological changes were evaluated by electroretinography (ERG) analysis and hematoxylin and eosin (H&E) staining, respectively. Massive photoreceptor and RPE cell death were examined by terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL). The damage to the retina was aggravated in the FOXO1 gene-knockdown and miR-27a-overexpression groups after exposure to LED but was alleviated in the FOXO1 gene-overexpression or miR-27a-knockdown groups. Dual luciferase assay was used to detect the binding site of miR-27a and FOXO1. Upregulated miR-27a inhibited the expression of FOXO1 by directly binding to the FOXO1 mRNA 3 ′ UTR and decreased the autophagy activity of ARPE-19 cells, resulting in the accumulation of reactive oxygen species (ROS) and decrease of cell viability. The results suggest that miR-27a is a negative regulator of FOXO1. Also, our data emphasize the prominent role of miR-27a/FOXO1 axis in modulating ROS accumulation and cell death in RPE cell model under oxidative stress and influencing the retinal function in the LED-induced RD rat model.